Pengaruh Media Sosial TikTok terhadap Minat Belajar Siswa MA Miftahul Ishlah Tembelok - Akhmad Asyari; Mirannisa Mirannisa (ISLAMIKA, 2022)
Audiovisually, Tik Tok is unique compared to other social media platforms. So it is not uncommon to use it as a learning medium because in addition to containing entertaining elements, it can also be a fun learning tool. This study aims to determine whether there is an effect of TikTok social media on students' interest in learning at MA Miftahul Ishlah Tembelok. This research uses correlation quantitative research or correlation research. Data collection techniques in this study were questionnaires, interviews, and documentation. This research is a population research with a total of 75 respondents. Hypothesis testing in this study used a simple linear regression test. Data management in this study uses the SPSS version 21 application. The results of this study indicate that the use of TikTok social media for students is in the medium category with a percentage of 59.5%. For learning interest, students are included in the medium category with a percentage of 61.9%. Based on the results of this study, it can be seen that the significance value is 0.000, so 0.000 <0.005, meaning Ho is rejected and Ha is accepted, so there is a positive and significant influence between TikTok social media and students' interest in learning at MA Miftahul Ishlah Tembelok. The influence of TikTok social media on students' interest in learning is 34.0%.